The Use of Chromebooks to Support Flipped Classroom Learning in English Lessons: A Descriptive Qualitative Study - Kurniawati, Sri Sulis (Samudra Publisher, 2025)
The integration of technology in education has become essential in the digital era, including the use of Chromebooks in English learning. This study aims to describe the implementation of a flipped classroom model supported by Google Classroom using Chromebooks at SMPN 9 Madiun. This research employed a descriptive qualitative approach with data collected through documentation, observation, and questionnaires. The findings indicate that Chromebooks facilitate learning accessibility, support student participation, and encourage independent learning before classroom activities. In addition, Google Classroom enables teachers to manage assignments and learning interactions more effectively. Overall, the integration of Chromebooks within the flipped classroom model enhances students’ motivation and engagement in English learning.